The Students’ Competence in English Grammar and Writing: A Corelative Study at the Second grade Students of MTs. Al-Muini, Sesela Gunungsari - Ismail Musa (Yayasan Baru Haji Samsudin, 2025)
This study is intended to discover the correlation between students’ grammar competence and their writing skill. The samples chose was the second grade students of MTs. Al-Muini Sesela consists 35 students. The students were given 25 questions in the form of multiple choice types on grammar competence test and they were asked to write at least 100 words about their experience in the form of paragraph on writing skill test. The procedure of collecting data was testing technique by using formula: rxy=????/(Xy2)x(Xy2). The result findings were: 1) the students’ average gets fairly good score in grammar competence test. It can be seen from the result of mean of the students’ score that was 6.76. 2) the students’ average get fairly good score in their writing skill test. It can be seen from the mean of the students’ score that was 6.74. 3) There is a correlation between the students’ grammar competence and their writing skill which can be observed from the value of “r” with N = 35 (r= 0.823) that was greater than the value of “r” at the table (r= 0.334) at the level of significance 5% and (r= 0.430) at the level of significance 1%. Therefore, the result shows that grammar competence has a high role in writing skill. It is clear that the Alternative hypothesis (Ha) which says “there is a correlation between students’ grammar competence and their writing skill was accepted